Pelatihan Recurrent Basic PKP-PK bagi Pegawai Badan Usaha Bandar Udara Hang Nadim-Batam - Wildan Nugraha; Anton Abdullah; Fitri Masitoh; Jafar Haris Muslim; Sutiyo Sutiyo (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2020)
In realizing Airport Rescue and Firefighting (ARFF) services at airport, it must be supported by competent and superior Human Resources (HR). Airport operators must ensure that all personnel employed at that airports receive adequate education and / or training to meet the airport personnel competency standards set by the Director General of Civil Aviation at PM 55 of 2015 concerning airports. To meet the requirements required by the regulation, Palembang Aviation Polytechnic as an organization engaged in education and training collaborates with the Batam Concession Agency in carrying out community service activities through ARFF recurrent basic training with 37 participants. The training aims to improve and refresh the skills and knowledge possessed by ARFF basic level personnel. All participants successfully passed with an average value of 81,10. Then, based on the results of the evaluation of the implementation of the training as well as a whole well.